Water Consumption on The Morning to Constipation of Patient with Immobilization - Deni Yasmara; Dewi Irawaty; I Made Kariasa (Universitas Airlangga, 2013)
Introduction: Patient with musculoskeletal disorder has been moving limitation and caused decreasing of gut peristaltic. The aimed of this study to find out the influence of drinking plain water 500 ml on the morning to constipation Incident of Immobilize Patient with musculoskeletal system disorder.Methods: The methode of this study were quasi-eksperiment with post test only non equivalent control group design. The number of sample was 24 respondents as intervention group, and 24 respondent as control group. The instrument that be used were Bowel Score that have been observed everyday for three days.Result: The result shows significant influences of drinking plain water on the morning to constipation incident of immobilize patient musculoskeletal system dysorder (p value=0.002; α=0.05.Conclusion: consuming water can avoid constipation on immobilize patient with musculoskeletal disorder. For the next research hopefully measures and analize psychosocial faktor of the patient defecation such as comfortable and privacy.